2012
DOI: 10.1111/j.1399-3046.2012.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with low physical activity levels following pediatric cardiac transplantation

Abstract: Pediatric cardiac transplantation recipients may be indicated to participate in cardiac rehabilitation to optimize physical activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 25 publications
4
22
1
Order By: Relevance
“…08957 x age (yr))–(0 . 000038 x counts/min x age (yr)) *One study [31] recruited healthy control and patient participants at the same time and measured MVPA and ST in the same way as (referred to here as studies with control group); 5 studies [27–29, 33, 34] compared patient data with other studies-previous published studies (referred to here as studies with comparison groups); and1 study [32] reported patient data in relation to recommendations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…08957 x age (yr))–(0 . 000038 x counts/min x age (yr)) *One study [31] recruited healthy control and patient participants at the same time and measured MVPA and ST in the same way as (referred to here as studies with control group); 5 studies [27–29, 33, 34] compared patient data with other studies-previous published studies (referred to here as studies with comparison groups); and1 study [32] reported patient data in relation to recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…This included children who had received different types of cardiac surgery [29, 31, 32], including complex surgery such as a fontan repair [28, 33, 34], or cardiac transplantation [27]. In all cases the patients were studied at least 6 months after surgery while well, clinically stable, free of acute illness, and living in the community.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐nine articles underwent full‐text review, with an additional 13 articles excluded due to participant age (n=7), lack of exercise testing (n=3), and articles not in English (n=3). A total of 16 studies were included in this systematic review: six prospective cross‐sectional, five retrospective longitudinal, four retrospective cross‐sectional, and one case series . Validity appraisal scores ranged from 6/9 to 8/9.…”
Section: Resultsmentioning
confidence: 99%
“…Banks et al [18] observed low moderate-to-vigorous physical activity (MVPA) levels in pediatric cardiac transplantation recipients. Banks et al [18] observed low moderate-to-vigorous physical activity (MVPA) levels in pediatric cardiac transplantation recipients.…”
Section: Research On Pediatric Transplantation Patientsmentioning
confidence: 99%